1997
DOI: 10.1159/000174105
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of Total and Zonal Glomerular Filtration Rate in Spontaneously Hypertensive Rats with Mesangiolysis

Abstract: In this study we tested the hypothesis that mesangial cells participate in autoregulation of the glomerular filtration rate (GFR) in normotensive and hypertensive rats. Mesangial cell lesions were induced by intravenous administration of antithymocyte (anti-Thy 1.1) antibodies in spontaneously hypertensive rats (SHR) and in Wistar-Kyoto rats (WKY). Normal murine serum was injected in control rats. Hemodynamic measurements were performed 24 h after the infusion of the anti-Thy 1.1 antibodies. Renal blood flow (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…These effects do not seem to be influenced by NO and of a magnitude sufficient to explain the GFR reduction in our study [33]. The importance of the mesangial cells in GFR autoregulation is convincingly demonstrated in a recent work from our group [34]. After inducing mesangiolysis by the anti-Thy-1-1 antibody, we demonstrated that the GFR declined substantially in SHR during pressure reduction, suggesting that the function of the mesangial cells is a requirement for normal autoregulation of GFR, at least in SHR.…”
Section: Discussionsupporting
confidence: 86%
“…These effects do not seem to be influenced by NO and of a magnitude sufficient to explain the GFR reduction in our study [33]. The importance of the mesangial cells in GFR autoregulation is convincingly demonstrated in a recent work from our group [34]. After inducing mesangiolysis by the anti-Thy-1-1 antibody, we demonstrated that the GFR declined substantially in SHR during pressure reduction, suggesting that the function of the mesangial cells is a requirement for normal autoregulation of GFR, at least in SHR.…”
Section: Discussionsupporting
confidence: 86%
“…By contrast, in hyperglycaemic subjects and animals, both myogenic response and tubuloglomerular feedback become compromised following the onset of hyperglycaemia, 19–22 resulting in progressive deterioration of renal auto‐regulation 20 . Considering the role of contractile mesangial cells in controlling RBF and GFR 9,10,23 one could envisage the increased role of mesangium in maintaining RBF and GFR after the onset of hyperglycaemia. However, hyperglycaemia has been demonstrated to decrease contractility of mesangial cells, 24,25 thus compromising their contribution to renal auto‐regulation.…”
Section: Discussionmentioning
confidence: 99%
“…(42,276,1167,1188,1241). Spontaneously hypertensive rats (SHR) had excellent RBF and GFR autoregulation (41,43,465,672,706,1247) and stable mean P GC and peritubular capillary pressures in their superficial cortical nephrons, which were attributed to proportionate adjustments in preglomerular vascular resistance with RPP (42, 58,394,1064,1247,1564,1567). Nevertheless, these SHR displayed a pressure-natriuresis, albeit dampened compared with normotensive Wistar-Kyoto (WKY) rats that also autoregulated efficiently (42,276,412,808).…”
Section: Pressure-natriuresismentioning
confidence: 99%
“…Nevertheless, efficient RBF autoregulation and the myogenic response in SHR was preserved in the absence of MD-TGF input during ureteral obstruction (297) and persisted after damage to mesangial cells by antithymocyte antibodies in both SHR and WKY, whereas autoregulation of GFR was attenuated (1564). Thus, although mesangial cells can participate in the regulation of GFR, likely via MD-TGF signaling, they do not seem to contribute to RBF autoregulation, which, in their absence, is maintained by enhanced myogenic tone.…”
Section: Shrmentioning
confidence: 99%